Bank risk-taking and impaired monetary policy transmission - Philipp J. Koenig; Eva Schliephake (European Central Bank (ECB), 2022)
We consider a standard banking model with agency frictions to simultaneously study the weakening and reversal of monetary transmission and banks' risk-taking in a low-interest environment. Both, weaker monetary transmission and higher risk-taking arise because lower policy rates impair banks' net worth. The pass-through to deposit rates, the level of excess reserves and the extent of the agency problem between banks and depositors are crucial determinants of monetary transmission. If the deposit pass-through is sufficiently impaired, a reversal rate exists. For policy rates below the reversal rate further interest rate reductions lead to a disproportionate increase in risk-taking and a contraction in loan supply.
Keywords: G21; E44; E52; 330; Monetary policy; Bank lending; Risk-taking channel; Reversal rate